Religious Character Building in Social Studies Learning through Internalization of Ahlussunnah wal Jamaah Values - Eldi Mulyana; Mamat Ruhimat; Agus Mulyana; Erlina Wiyanarti (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
The role of Social Studies teachers in internalising the value of Ahlussunnah wal Jamaah aims to form a religious character in students. Qualitative approach through phenomenological method by means of observation, in-depth interviews, and documentation studies. The results show that the school conducts the process of internalizing Ahlussunnah wal Jamaah values by habituating students to be moderate, tolerant, balanced, and inviting goodness while preventing evil. Social Studies teachers facilitate the internalization of Ahlussunnah wal Jamaah values through the stages of value transformation, value transactions, and value internalization. The limitations of inadequate technological facilities still hinder the Social Studies learning process. The results of this study indicate that, in the learning process, social studies teachers are not only focused on cognitive and psychomotor aspects as learning outcomes, but also should pay attention to affective aspects, which become an important factor in shaping the religious character of students.